Bahaya Pergaulan Bebas Pada Remaja - Dealita Khairani Daulay; Linawati Togatorop; Armando B. Sianturi; Ledi Isni Pasaribu; Josua Alvarait Lumban gaol; Yemima Stefany Duha; Sophia De Laura Pasaribu; Syatrio Pradana (STIKES Columbia Asia Medan, 2025)
Promiscuity is a common issue among adolescents, as a transitional phase that is highly susceptible to environmental influences, directly impacting physical, mental, and social health. Lack of understanding of the impacts of promiscuity can increase health risks for adolescents, including increased risk of sexually transmitted infections (STIs), unplanned pregnancy, organ damage due to addictive substances (narcotics), mental health disorders, and decreased social and academic functioning. This health promotion activity was conducted at Free Methodist 1 Junior High School in Medan as a form of early education and prevention. The goal was to increase students' knowledge and awareness of the dangers of promiscuity and encourage healthier and more responsible behavior. The method used was preventive education through lectures, discussions, and interactive Q&A sessions. The results of this activity showed an increase in student understanding of the material, for example, understanding of promiscuity increased from 70% to 85% and understanding of drug abuse from 62% to 67.5%, as well as the importance of developing a healthy lifestyle, avoiding harmful substances, and maintaining overall physical, mental, and social health